Xanthones and coumarins from the twigs of Mesua ferrea L. - Chakthong, Suda; Chukaew, Arnon; Saithong, Saowanit; Chusri , Sasitorn; Limsuwan, Surasak; P. Voravuthikunchai, Supayang (Progress in Applied Science and Technology, 2020)
Five xanthones 1-5 and four phenylcoumarins 6-9 were isolated from acetone extracts of twigs of Mesua ferrea L. The structures of these compounds were elucidated by spectroscopic analysis and comparison with reported data such as 1D and 2D NMR, UV and IR spectroscopy. Compounds 4-7 were isolated from this plant for the first time. Compound 3, 1,5,6-trihydroxyxanthone, showed significant antioxidant activities with IC50 values of free radical scavenging in DPPH and ABTS assays of 45.0 and 197.0 μg/mL, respectively, as compared to the control, trolox, (77.6±1.0 µg/mL and 282.9±1.2 µg/mL for DPPH and ABTS assay, respectively). Besides, mammea A/AA cyclo F, compound 9, formed in a single crystal and was reported.